An Unhurried View of Copyright - Kaplan, Benjamin 1911-2010 (James S. Carpentier Lectures, 1967)
A series of lectures given by Kaplan, in which he examines the notions of copyright and its infringement in order to determine the criteria for creating public policy concerning copyright protection